Acute Pancreatitis-Induced Thrombotic Thrombocytopenic Purpura - Gurjar, Mohan; Saigal, Saurabh; Azim, Afzal; Mohindra, Samir; Prasad, Narayan; Srivastava, Gaurav (JOP. Journal of the Pancreas, 2012)
<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Context<span style="font-size: 8.0pt; font-family: Verdana; mso-fareast-font-family: "Times New Roman"; mso-bidi-font-family: "Times New Roman"; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US"> Acute pancreatitis due to thrombotic thrombocytopenic purpura is a well recognized condition. Here, we are reporting a rare converse phenomenon, in which thrombocytopenic purpura occurred secondary to acute pancreatitis. Case report A 19-year-old male referred to our intensive care unit with diagnosis of acute pancreatitis with multi-organ dysfunction. He had history of severe abdominal pain and recurrent vomiting about one month ago, requiring hospital admission. There, on diagnostic work-up at admission, abdominal ultrasonography was suggestive of pancreatitis. His serum amylase and lipase were 1,900 and 1,582 U/L, respectively. Other laboratory parameters were within normal limits. He was managed conservatively with intravenous fluids, antibiotics and analgesics; and discharged after about 2 weeks One week after discharge he was readmitted in same hospital with abdominal pain, multiple episodes of bilious vomiting and abdominal distention. Later on he was referred to our intensive care unit; having classical pentad of thrombocytopenic purpura, i.e., thrombocytopenia, micro-angiopathic hemolytic anemia, renal failure, encephalopathy, and fever. His condition improved with plasma exchange therapy and transferred out from our ICU to ward after 10 days of stay. Conclusion Thrombocytopenic purpura may be precipitate by acute pancreatitis due to multiple mechanisms. A high clinical suspicion is required to make an early diagnosis and allow early initiation of plasma exchange therapy, resulting in a good prognosis.